Assessment of antioxidant, antimicrobial and anti-osteosarcoma potential of four traditionally used Indian medicinal plants - Nayak, Debasis; Ashe, Sarbani; Rauta, Pradipta Ranjan; Nayak, Bismita (Journal of Applied Biomedicine, 2017)
In the present investigation Hibiscus rosa-sinensis (petals), Acorus calamus (rhizome), Moringa oleifera (leaves) and Cucurbita maxima (petals) were screened for their efficacy against osteosarcoma with elucidating a mechanism of their anticancer potentiality. The methanolic plant extracts revealed the presence of all major phytochemicals with quantitative analysis of flavonoids (98.15 ± 2.02 to 12.34 ± 0.57 mg of RUE/g) and total phenolics (26.40 ± 0.11 to 8.54 ± 0.10 mg of GAE/g). The antioxidant activity was assessed by standard DPPH, H2O2 scavenging, NO scavenging assays. The hemolysis, hemagglutination, and erythrocyte aggregation assays unveiled their compatibility with blood components. As most of the opportunistic microbes infect subsequently immunocompromised patients, the antimicrobial activity of the plant extracts showed a zone of inhibition (in mm) against nosocomial strains of Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa and Vibrio cholerae having MIC between 12.5–50 μg/ml. Through MTT assay the IC50 value was calculated against MG 63 osteosarcoma with detailed studies on DNA fragmentation and chromatin condensation, revealing apoptosis being their primary mode of anticancer effect. Further the migration and colony forming assays supported the anticancer potentials of the methanolic plant extracts. The cell cycle analysis revealed that A. calamus and M. oleifera extracts were capable of arresting the growth of MG 63 osteosarcoma cells.
Keywords: Cucurbita; puškvorec; screeningové testy protinádorových léčiv; Osteosarcoma; In Vitro Techniques; Moringa; nádorové buňky kultivované; léčivé rostliny; techniky in vitro; osteosarkom; rostlinné extrakty; Plants, Medicinal; antioxidancia; Microbial Sensitivity Tests; Acorus; fytoterapie; mikrobiální testy citlivosti; Antineoplastic Agents, Phytogenic; Hibiscus; fytogenní protinádorové látky; Plant Extracts; Drug Screening Assays, Antitumor; Phytotherapy; Antioxidants; Tumor Cells, Cultured